Promoting an educational and reflective space on health promotion and disease prevention practices - Germani, Alessandra (Guará Journal, 2018)
Scientific  dissemination  is  the  way  to  expand  access to  scientific  knowledge  for  society  as  a  whole,  in order  to  help  solve  various social problems and bring the citizen closer to science. At the Federal University of Amapá-Unifap, there is a noticeable lack of dissemination of research. In this sense, we present the extension project  Agency  of  Scientific  Journalism, Science  Unifap.  The  proposal developed a website with journalistic content involving the scientific and technological production of Unifap researchers. The project was developed based on research on strategies of scientif-ic dissemination in the field of public communication, the study of institutional  production carried  out  by  the  communications  sector of Unifap, as well as experiences in scientific dissemination by public institutions. The production of content took as a reference the  specifics  of  webjournalism,  especially the  tendency  to  multi-media production, using accessible language, addressing issues of public interest.
Keywords: University extension; Health promotion; Prevention of diseases